Towards self-adaptable intelligent assembly systems - Antzoulatos, Nikolas (2017)
Currently, European small and medium-sized enterprises (SMEs) are experiencing increasing pressure to provide high quality goods with customised features while at the same time remain cost effective and competitive in the global market. In the future, manufacturing systems need to be able to cope with constantly changing market requirements. Consequently, there is a need to develop the research foundations for a new generation of manufacturing systems composed of intelligent autonomous entities which are able to reconfigure themselves and to adapt their performance as a result of product and environmental changes.